2017
DOI: 10.1073/pnas.1620316114
|View full text |Cite
|
Sign up to set email alerts
|

Ion and inhibitor binding of the double-ring ion selectivity filter of the mitochondrial calcium uniporter

Abstract: The calcium (Ca 2+ ) uniporter of mitochondria is a holocomplex consisting of the Ca 2+ -conducting channel, known as mitochondrial calcium uniporter (MCU), and several accessory and regulatory components. A previous electrophysiology study found that the uniporter has high Ca 2+ selectivity and conductance and this depends critically on the conserved amino acid sequence motif, DXXE (Asp-X-X-Glu) of MCU. A recent NMR structure of the MCU channel from Caenorhabditis elegans revealed that the DXXE forms two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 45 publications
4
59
0
Order By: Relevance
“…MCU contains two trans-membrane helices, with amino and carboxyl termini facing into the matrix, with a short hydrophilic stretch of amino acids (YSWDI) linking them at the mouth of the channel facing the mitochondrial intermembrane space (Baughman et al, 2011; De Stefani et al, 2011). This region of the channel has highly conserved acidic residues, including an aspartate in position 261 that is involved in Ca 2+ permeation and selectivity (Cao et al, 2017; Chaudhuri and Clapham, 2014; Oxenoid et al, 2016). To predict a drug-target interaction and to identify key residues, we performed molecular docking using the YSWDI motif in the pentameric C. elegans MCU pore structure (Oxenoid et al, 2016) (Figure 7E).…”
Section: Resultsmentioning
confidence: 99%
“…MCU contains two trans-membrane helices, with amino and carboxyl termini facing into the matrix, with a short hydrophilic stretch of amino acids (YSWDI) linking them at the mouth of the channel facing the mitochondrial intermembrane space (Baughman et al, 2011; De Stefani et al, 2011). This region of the channel has highly conserved acidic residues, including an aspartate in position 261 that is involved in Ca 2+ permeation and selectivity (Cao et al, 2017; Chaudhuri and Clapham, 2014; Oxenoid et al, 2016). To predict a drug-target interaction and to identify key residues, we performed molecular docking using the YSWDI motif in the pentameric C. elegans MCU pore structure (Oxenoid et al, 2016) (Figure 7E).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the uniplex modulators were limited to lanthanides and ruthenium-related compounds, which had been shown to inhibit the (Anghileri, 1975;Cao et al, 2017;Kirichok et al, 2004;Moore, 1971). Ru360 and RuR ( (Cao et al, 2017).…”
Section: Pharmacological Inhibitors Of the Mcumentioning
confidence: 99%
“…The ubiquitously expressed MCU is a~35 kDa protein containing two transmembrane domains (TMDs) that are linked by a highly conserved sequence ( Figure 1b). The channel formed by MCU is sensitive to ruthenium red (RuR), RU360, and lanthanides (Cao, Wang, Cui, Su, & Chou, 2017;Crompton, Heid, Baschera, & Carafoli, 1979;De Stefani et al, 2011). The channel formed by MCU is sensitive to ruthenium red (RuR), RU360, and lanthanides (Cao, Wang, Cui, Su, & Chou, 2017;Crompton, Heid, Baschera, & Carafoli, 1979;De Stefani et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these observations confirmed that MCU is the Ca 2+ -conducting pore of the long-sought mitochondrial uniporter. Moreover, recent studies on the structural biology (Oxenoid et al 2016), coordination chemistry and molecular dynamics (Cao et al 2017) of MCU from Caenorhabditis elegans suggested that a functional channel results from the pentameric assembly of MCU multimers stabilized by a coiled-coil motif protruding into the mitochondrial matrix. In this structural model, the DIME motif forms the selectivity filter of the channel, whereby ion permeation and inhibitor binding occur.…”
Section: The Mitochondrial Ca 2+ Uniportermentioning
confidence: 99%